Calcifying epithelial odontogenic tumor, a rare presentation in children: Two case reports - Susant Mohanty; Neeta Mohanty; Samapika Routray; Satya Ranjan Misra; Vijeev Vasudevan (Wolters Kluwer Medknow Publications, 2014)
Calcifying epithelial odontogenic tumor (CEOT) is a rare and benign odontogenic neoplasm that affects the jaws. It is certainly an atypical instance to find this tumor in children. Here, we present two case reports of CEOT presenting in mandible of a 12- and 13-year-old female child, respectively. CEOT have been reported to show features of malignant transformation also.